TRANSPARENCY AND ACCOUNTABILITY IN THE MANAGEMENT OF NONPROFIT ORGANIZATION FINANCES - Citra Putranti, Ellyn (DIVERSITY Logic Journal Multidisciplinary, 2024)
Background. Transparency and accountability in financial reporting are crucial aspects for nonprofit organizations, which will impact the public's perception of the organization, either positively or negatively. Research Purpose. This study examines the importance of financial transparency and accountability in maintaining public trust in nonprofit organizations. Research Method. A qualitative approach with descriptive methods is employed, gathering comprehensive data systematically, followed by qualitative analysis to achieve clarity of the research objectives. In conducting research, data collection is used using library research by studying scientific journals, research results and PSAK related to the problem of the object being studied. The sources used will be used as a guide and basis for this research Findings. The findings indicate that accountability and transparency practiced by nonprofit organizations in publishing financial reports enhance public trust, leading to their prosperity and positively impacting their operational sustainability. Nonprofit organizations are not immune to major cases resulting from suspicion and mismanagement, thus maintaining financial accountability and transparency is crucial to prevent these challenges from undermining public trust and avoiding suspicion and mismanagement in their activities. Conclusion. The research recommendation is to increase information to obtain more comprehensive data related to horizontal accountability. This can be achieved by adding data collection techniques such as distributing questionnaires to the public.